Hurdels to cross for the 'jadibuti' cultivation of Nepal: A case study of Karnali, Midwestern Nepal - Rai, S. K. (Journal of Plant Resources, 2009)
No abstract available. <!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]-->Bulletin of the Department of Plant Resources Vol 30, 2008 pp 105-108